Occurrence of Dirphia araucariae in Araucaria angustifolia in the municipality of Congonhinhas, PR, Brazil - Borges, Jácomo Divino; Macedo, José Henrique Pedrosa (Pesquisa Agropecuaria Brasileira, 2014)
This paper presents information on an important pest of Araucaria angustifolia (Bertoloni) O. Kuntze; Damages of Dirphia araucariae Jones. 1908 (Lepidoptera, Attacidae) in trees of Brazilian pine, occurred in the year of 1979 in the municipality of Congonhinhas, State of Paraná, Brazil, an studies its biology and behavior. The area of attack was 90 ha, with 200,000 trees.
Keywords: evolutive cycle; forestry entomology; Lepidoptera; Brazilian pine